Comportamiento agronómico del cultivo de soya (Glycine max L.) a la aplicación de tres bioestimulantes, en la zona de Babahoyo - Lanche Monar, Ángel Eliecer (2012)
The soybean (Glycine max. L) it is characterized for being a legume of short cycle extensively cultivated in Ecuador, constituting itself in one of the raw materials more using in the agro-industry and the human feeding. In Ecuador the zones of greater production are Babahoyo and Montalvo where altogether 40,000 were seeded has. The objective of this investigation was to evaluate the effectiveness of the application of several biofertilizantes on the yield and behavior of the culture and to realize an economic analysis. The work was realized in the experimental fields of the farm “San Pablo”, located in the Technical University of Babahoyo, Farming Faculty of Sciences in the Province of Los Ríos. Ten treatments and 3 repetitions were investigated. Seedtime of soya was realized with variety INIAP-307, in 16 parcels of m2. The treatments were distributed at random in a design of complete blocks. For the evaluation of averages the test of Tukey to 5% of probability was used. At the end of the cycle of the culture it was evaluated: height of plants, height of load, evaluation of grain diseases, days to flowering, number of cases by plant, days to harvest, number of grains by case, weight 1000 seeds, foliar analysis and yield by hectare.